Managed Play: The Media's Impact on Play in the Australian Football League - Duncan Samuel Keith (Sciendo, 2018)
No industry has influenced the transformation of the Australian Football League (AFL) into a professional, commercial business more than the media. Today, the AFL players are paid more than ever and are used as marketing tools to promote and sell the game, often to new fans in new markets of Australia - namely New South Wales and Queensland - who haven't traditionally played Australian Football, preferring the rugby codes instead. But perhaps the biggest change in the AFL is that the play element is now used as function of business. Put simply, winning leads to more money. As such, the play element is now manipulated more than ever. The game has more coaches implementing more tactics, strategies, game plans and set plays than ever before. These changes can be linked back to the media's influence on the game. This paper utilises the combined observations and theories of Johan Huizinga and Pierre Bourdieu to create a theoretical lens through which we can understand the media's growing influence in sport and its impact on play's transformation. The theory will then be expounded through an extensive analysis of the media's influence in the AFL, particularly its play element. This analysis will be supported with insights and views from AFL fans, members, commentators and theorists.